China Shocks and Their Employment Effects in Emerging Economies - Bambang Suprayogi; Tarek M Harchaoui (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2020)
The impact of “China shocks” on trading partners is a source of a massive supply shock that displaces foreign manufacturing producers, and an important source of demand shock that propelled forward a wide range of foreign sectors. The “common” existing literature mainly focused on the supply shock and its impact, leaving a large span of “China shocks” unexplained. Thus, this article undertake the important task to account for the dual track of “China shocks” and their impacts on a set of emerging economies, for which the evidence remains scanty. Using a global input-output methodology which highlights the job creation from exports and the job destruction aspect of imports, we provide evidence on the employment effect of bilateral trade with China. Our results suggest that considering the net effect of supply and demand related to China shocks mainly lead to negative job demand, and press the ringing bell for the government.JEL Classification: F1, F16, F66How to Cite:Suprayogi, B., & Harchaoui, T. M. (2020). China Shocks and Their Employment Effects in Emerging Economies. Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 31-50. doi: http://dx.doi.org/10.15408/sjie.v9i1.13550.